ΑΛΗΘΙΝΟΣ ('HIGH QUALITY') IN AMPHIS, FR. 26 AND OTHER LATE CLASSICAL AND EARLY HELLENISTIC AUTHORS. (6th February 2019) - Olson, S. Douglas
Abstract : LSJ s.v. A defines ἀληθινός as meaning 'truthful, trusty' of persons and 'true, genuine' of objects, and offers Amphis, fr. 26 (preserved at Ath. Deipn. 2.57b and 7.277c, and identified in the latter passage as drawn from a play entitled Leukas ) as an example of the second sense:ὅστις ἀγοράζων ὄψον <- x- ˘ -> ἐξὸν ἀπολαύειν ἰχθύων ἀληθινῶν ῥαφανῖδας ἐπιθυμεῖ πρίασθαι, μαίνεται Anyone who, when shopping for dainties … wants to purchase radishes, when he has a chance to enjoy alêthinoi fish, is crazy. The context of the fragment is unknown. But the speaker is patently drawing a contrast not between 'real fish' and something that resembles fish ('false fish'), as LSJ would have it, but between a type of fish that any sensible person would buy for dinner, should the opportunity arise, and radishes, which are edible but unexciting fare. So too at Macho 28–32, when King Ptolemy's guests were served a variegated rockfish (πετραίου … ποικίλου), three κωβιοί cut into steaks, and καράβων … ἀληθινῶν (29)—literally 'real crayfish'—they were astonished and delighted. The reaction suggests that the banqueters were happy because the crayfish Ptolemy served matched the quality of the other seafood he set before them, not because the king had declined to deceive them ( sc . by serving a different food disguised as crayfish).